Phenotypic Variability among Chilli Germplasms Using Shannon-Weiner Index (H’) - Bal, Solanki; Chattopadhyay, Arup; Mandal, Asit Kumar (International Journal of Bio-resource and Stress Management, 2024)
The investigation was conducted during the rabi season (September 2019 to February 2020) of 2019 to 2020 at the research field of All India Co-ordinated Vegetable Crops, located at Bidhan Chandra Krishi Viswavidyalaya in Kalyani, Nadia, West Bengal, India. The aim of the study was to examine the characteristics of twenty-six chilli genotypes across twelve qualitative traits. The investigation unveiled a broad range of phenotypic variability using Randomized Block Design in three replications. Among the assessed traits, leaf density, leaf shape, fruit shape, plant habit, fruit curvature, and anther colour exhibited the most extensive variations among the genotypes. Conversely, the traits with the least diversity values, all falling below the overall mean, included fruit surface (0.28%), leaf colour (0.42%), stem pubescence (0.42%), stem colour (0.42%), anthocyanin colouration at nodes (0.48%), and leaf pubescence (0.48%). The Shannon-Weiner Diversity Index (H') ranged from 0.28 to 1.07. Of the traits evaluated, leaf density displayed the highest diversity index (1.07), followed by leaf shape (1.05), fruit shape (1.01), plant habit (0.86), fruit curvature (0.69), and anther colour (0.58). The obtained Shannon-Weiner Diversity Index, with an average value of 64.66%, confirmed the presence of significant diversity within the examined chilli genotypes. The results suggest that the indirect selection of chilli parent plants based on a range of morphological characteristics can offer advantages in the management of both biotic and abiotic stresses. The information holds significant value for effective pre-breeding, management, and utilization in crop improvement initiatives, in addition to augmenting the genetic potential of the crop.